2022
DOI: 10.1021/acssuschemeng.2c01969
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Life Cycle Assessment of Hardmetal Chemical Recycling Routes

Abstract: Secondary hardmetal is a large part of the supply for new hardmetal products, yet the environmental impacts of hardmetal recycling remain unknown to a large degree. The goal of this study was to evaluate the gate-to-gate impacts of tungsten and cobalt recovery by chemical recycling. The LCI data was obtained from process simulations and the environmental impact categories were calculated using GaBi software. The simulations were used to study process performance and to investigate the effect of process paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The feed into the recycling processes was the leach residue that remains after cobalt has been leached out of the residue left after leaching of oxidized hard metal scrap. The feed composition was based on the residue composition in hard metal chemical recycling modeled by Aromaa et al 14 The hard metal scrap composition was 11% by weight Co, 0.5% Cr 3 C 2 , 0.2% VC, 2.5% TaC, TiC, and NbC, with the remainder being WC. After two leaching steps to recover first tungsten and then cobalt, the remaining residue contains 20.2 and 24.2 wt % of the tantalum and niobium compounds, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feed into the recycling processes was the leach residue that remains after cobalt has been leached out of the residue left after leaching of oxidized hard metal scrap. The feed composition was based on the residue composition in hard metal chemical recycling modeled by Aromaa et al 14 The hard metal scrap composition was 11% by weight Co, 0.5% Cr 3 C 2 , 0.2% VC, 2.5% TaC, TiC, and NbC, with the remainder being WC. After two leaching steps to recover first tungsten and then cobalt, the remaining residue contains 20.2 and 24.2 wt % of the tantalum and niobium compounds, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In the absence of primary data, process simulation can be used to collect LCI data and study the impacts of metallurgical processes. The specific methodology has been demonstrated in several studies. , In this work, simulation parameters such as process conditions, reagent concentrations, and yields were mainly gathered from the literature on laboratory-scale processes or estimated based on knowledge of similar hydrometallurgical operation. This was considered in the uncertainty and sensitivity analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the proposed recycling processes should be critically analyzed from the perspective of environmental impacts. The Life Cycle Assessment (LCA) is a standardized methodology extensively used to study the environmental impacts of a product, process, or activity [28], and it is also increasingly used to evaluate the environmental impacts of metal recycling processes [29,30]. The combination of LCA and economic analysis would create a systematic evaluation method and help in optimizing the recycling routes.…”
Section: Further Considerationsmentioning
confidence: 99%
“…Data on technical and economic efficiency of the hardmetal recycling processes of industrial interest were scarce till a few years ago, as they were strictly related to strategic proprietary know-how. Recently, some studies have been published that disclose interesting information about life cycle inventory (LCI) and life cycle assessment (LCA) [22,23], although a direct comparison of the competing processes still relied on strong assumptions. Nonetheless, it has been demonstrated that, compared to primary production, the elaborate chemical recycling process allows a decrease in impacts by more than 50% [23].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, alkaline electrolytes [56][57][58][59][60][61] dissolve WC readily at the anode, that can be recovered later as tungstic acid, while Co, again, is electroplated on the cathode. Potentiostatic [45,47,49,[51][52][53]60,61] and galvanostatic [45,48,50,56,58] approaches have been explored with both acidic and alkaline electrolytes, but no industrially viable process resulted from these studies [23,62]. In the literature on electrochemical recovery processes, the pseudopassivation layer phenomenon is observed but not well studied.…”
Section: Introductionmentioning
confidence: 99%